Les postures d’enseignant·e·s relatives à la branche « Ethique et Cultures Religieuses » en Suisse romande sous le prisme de la neutralité - Melissa Girardet; Elisabeth Ansen Zeder; Petra Bleisch (Éducation et Socialisation)
In French-speaking Switzerland, the new school subject “Ethics and Religious Cultures” (ARC), introduced between 2011 et 2014, is not treated in the same way as the other school subjects by the teachers, to the point of sometimes being completely overlooked, mainly for lack of a real understanding of the aims of the subject and of what is expected of them. The ERC thus encounters significant obstacles and limits on which we attempt to provide explanations by focusing on the stances adopted by teachers concerning ERC. We have identified 9 teaching stances from our data which we organize according to 3 aspects relating to ERC. The presentation of the teacher’s stances will lead us to reflect on the notion of neutrality in teaching ethics and on religions – a question that preoccupies many of the actors we met, and which is also debated in both the political and scientific fields.